2022
DOI: 10.1016/j.jtcme.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Potential natural products that target the SARS-CoV-2 spike protein identified by structure-based virtual screening, isothermal titration calorimetry and lentivirus particles pseudotyped (Vpp) infection assay

Abstract: Background and aim Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) enters cells through the binding of the viral spike protein with human angiotensin-converting enzyme 2 (ACE2), resulting in the development of coronavirus disease 2019 (COVID-19). To date, few antiviral drugs are available that can effectively block viral infection. This study aimed to identify potential natural products from Taiwan Database of Extracts and Compounds (TDEC) that may prevent the binding of viral spike p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Computational studies showed that catechin and curcumin bind the interface of the ‘RBD:ACE2-complex’, suggesting the efficacy of these two polyphenols in hindering the formation of SP and ACE2 complex [ 45 ]. Structure-based virtual screening of the Taiwan Database of Extracts and Compounds identified 39 natural products targeting the viral receptor-binding domain (RBD) of the SARS-CoV-2 spike protein; among them, amentoflavone was selected as the best one [ 46 ]. Recently, surface plasmon resonance of candidate molecular binders has been performed to determine the binding affinities and kinetics for RBD of a group of five compounds previously selected by a virtual screening of a natural product database, one of which was 5,4′-di-hydroxy-6,7-di-glucosyl-flavanone [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Computational studies showed that catechin and curcumin bind the interface of the ‘RBD:ACE2-complex’, suggesting the efficacy of these two polyphenols in hindering the formation of SP and ACE2 complex [ 45 ]. Structure-based virtual screening of the Taiwan Database of Extracts and Compounds identified 39 natural products targeting the viral receptor-binding domain (RBD) of the SARS-CoV-2 spike protein; among them, amentoflavone was selected as the best one [ 46 ]. Recently, surface plasmon resonance of candidate molecular binders has been performed to determine the binding affinities and kinetics for RBD of a group of five compounds previously selected by a virtual screening of a natural product database, one of which was 5,4′-di-hydroxy-6,7-di-glucosyl-flavanone [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…We then investigated the binding affinity of KC for the spike S1 RBD and the ACE2 receptor using the BLItz system, and found that KC had equilibrium dissociation constants ( K D ) of 5.03 × 10 −4 M for the spike S1 RBD and 8.11 × 10 −4 M for the ACE2 receptor ( Figure 2 and Table 1 ). Collectively, most of the natural product-derived inhibitors targeting the spike S1 RBD:ACE2 receptor interaction have been investigated based on in silico simulation [ 29 , 39 , 40 , 41 , 42 , 43 ]; however, this study not only provides information on a building block of COVID-19 therapeutic agents with the MoA that inhibits SARS-CoV-2 cell entry based on the actual molecular interaction between KC and the spike S1 RBD/ACE2 receptor, it also suggests that further structural analysis of KC derivatives is warranted to obtain increased binding affinity for both proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the direct interaction between celastrol and viral targets can also mediate its antiviral activity (Caruso, Singh, et al, 2020 ; Gupta et al, 2021 ), we demonstrated its potential ability to bind to essential targets to the viral life cycle. Interestingly, Chen and collaborators (Chen et al, 2022 ) experimentally demonstrated that celastrol binds to the S1 domain of SARS‐CoV‐2 spike protein ( K d = 1.712 µM) and inhibits the viral infection rate of ACE2 overexpressing 293T cell infected with lentivirus particles pseudotyped with SARS‐CoV‐2 spike. A previous study has described the celastrol interaction with the catalytic site of the SARS‐CoV M pro (Ryu et al, 2010 ), and here, we demonstrated the irreversibility of celastrol inhibition.…”
Section: Discussionmentioning
confidence: 99%